Clustering Predicts Memory Performance in Networks of Spiking and Non-Spiking Neurons - Chen, Weiliang; Maex, Reinoud; Adams, Rod; Steuber, Volker; Calcraft, Lee; Davey, Neil (Frontiers in Computational Neuroscience, 2011)
The problem we address in this paper is that of finding effective and parsimonious patterns of connectivity in sparse associative memories. This problem must be addressed in real neuronal systems, so that results in artificial systems could throw light on real systems. We show that there are efficient patterns of connectivity and that these patterns are effective in models with either spiking or non-spiking neurons. This suggests that there may be some underlying general principles governing good connectivity in such networks. We also show that the clustering of the network, measured by Clustering Coefficient, has a strong linear correlation to the performance of associative memory. This result is important since a purely static measure of network connectivity appears to determine an important dynamic property of the network.